Sea Levels: change and variability during warm intervals - EDWARDS, ROBIN JAMES (Sage, 2006)
The challenges associated with understanding precisely how climate affects sea level have been regular features of Progress Reports since the 1990s (e.g. Woodroffe, 1993; 1994, Woodroffe & Nash, 1995; Long, 2000; 2001; 2003; Edwards, 2005). Warm intervals like the Holocene are generally associated with high sea levels, but quantifying precisely how high these levels were, how quickly they were attained and what volumes or sources of water were involved remain important foci of research. These issues are of critical importance given current concerns about climate change, and the fact that oceanic thermal inertia seems to mean future rises are inevitable (Wigley, 2005). This review examines developments in our understanding of interglacial, postglacial and recent changes in sea level, with particular reference to the information provided by sea level highstands. These are compared with new data from a series of studies concerned with changes in the Greenland and Antarctic ice sheets. The picture of variability emerging poses particular challenges for models seeking to predict future trajectories of change.
PUBLISHED
Keywords: Oceanography; Climatic research